Research of thermal properties of brick and solutions applied to the laying of household furnaces - Chernevich О. В.; Bychenok И. И. (Chrezvychaynye situatsii: obrazovanie i nauka, 2006)
Researches of thermal properties of a ceramic brick and the solution used for laying of household furnaces are presented. It is established, that thermostability of a ceramic brick is low and essentially does not depend on its mark, and application of laying solutions on the basis of clay and sand is undesirable for setting fire chamber and smoke channels of the furnace.